Heterogeneous Nucleation of Calcium Carbonate: Effects of Sub- strate Chemistry - Nikolajsen, Lasse V. (UCPH NanoScience - a student research journal, 2018)
Investigating heterogeneous calcium carbonate nucleation is essential in the pursuit to the barriers of nucleation. However, heterogeneous calcium carbonate systems are difficult to characterize due to the influence of homogeneous nucleation. Homogeneous nucleation must be removed in order to reliably report the saturation indices used in the experiments. In this paper, homogeneous nucleation and heterogeneous nucleation are experimentally examined with atomic absorption spectroscopy, optical microscopy and ultraviolet-visible spectroscopy. The impact of homogeneous nucleation on concen- tration and the correlation between concentration and induction time are investigated. We document a significant impact on concentration suggesting data from current literature is compromised. Based on data, we propose a concentration range of 0.7 mM – 0.9 mM for obtaining barriers to nucleation using optical microscopy. Learning how surfaces influence the barriers and kinetics of CaCO3 nucleation can increase our understanding of biomineralization and improve carbon sequestration.